Kinetics and mechanism of the induced redox reaction of [Ni(cyclam)](2+) promoted by SO5 center dot- - Pezza, Helena Redigolo [UNESP]; Coichev, N. (Gordon Breach Sci Publ Ltd, 1999)
Oxidation of [Ni(cyclam)](2+), cyclam = 1,4,8,11-tetraazacyclotetradecane, accelerated by sulfur dioxide, was studied spectrophotometrically by following the formation of [Ni(cyclam)](3+) under the conditions: [Ni(cyclam)](2+) = 6.0 x 10(-3) M; initial [Ni(cyclam)](3+) = 8.0 x 10(-6) M; [cyclam] = 6.0 x 10(-3) M; [SO2] = (1.0-5.0) x 10(-4) M and 1.0 M perchloric acid in oxygen saturated solutions at 25.0 degrees C and ionic strength = 1.0 M. The oxidation reaction exhibits autocatalytic behavior in which the induction period depends on the initial Ni(III) concentration. A kinetic study of the reduction of Ni(III) by SO2 under anaerobic conditions, and the oxidation of Ni(II), showed that the rate-determining step involves reduction of Ni(III) by SO2 to produce the SO3.- radical, which rapidly reacts with dissolved oxygen to produce SO5.- and rapidly oxidizes Ni(II). The results clearly show a redox cycling process which depends on the balance of SO2 and oxygen concentrations in solution.
Keywords: nickel; cyclam; sulfur dioxide; peroximonosulfate